Eredoctoraat prof. mr. Geert Corstens, 17 oktober 2023. - Corstens, G. J. M.; Schutgens, R. J. B. (Roel Joseph Basile), 1978- (Radboud University Press, 2023)
On October 17, 2023, during the 100th Dies Natalis of Radboud University, Geert Corstens received an honorary doctorate from Radboud University. This honorary doctorate was awarded to him because of his tireless efforts for a strong, fair and equal constitutional state. This edition includes the laudation of honorary supervisor Roel Schutgens, the acceptance speech of Geert Corstens and the Van der Grint lecture given by Geert Corstens during the week of the Dies Natalis. Geert Corstens was president of the Supreme Court of the Netherlands from 2008 to 2014. Immediately after his appointment, he was known for his assertive attitude towards the political apparatus. The independence of the constitutional state should not be threatened by the wishes and needs of politicians and other outsiders, Corstens believed. He has also made a formidable contribution to public-oriented communication and explanation of the rule of law. Corstens also wrote, among other things, the books Our constitutional state and The judge seizes power: And other misconceptions about the democratic constitutional state to promote general communication about rights and democracy in the Netherlands. Corstens is also the author of the standard work Dutch criminal procedural law and was professor of criminal law at Radboud University from 1982 to 1995.
Keywords: Corstens, G. J. M.; Speeches, addresses, etc.; Criminal law.; Criminal procedure.; Discours.; speeches (documents)